The Relationship between Demographic Characteristics and Patient Compliance Undergoing Tuberculosis (Tbc) Treatment at the Bintuhan Health Center, Kaur Regency, Bengkulu Province - Riana Versita; Nova Yustisia; Suci Rachmawati; Cendy Felya Nengsih (ANJANI Journal (Medical Science & Healthcare Studies), 2021)
Tuberculosis (TB) is an infectious disease caused by the Mycobacterium tuberculosis bacteria. Adherence to long-term TB treatment is key to controlling tuberculosis. Non-compliance is a serious problem that often occurs which causes the therapeutic goals not to be achieved. This study aims to measure the level of patient compliance with the use of anti-TB drugs. This research was conducted at the Bintuhan Health Center, Kaur Regency. This research is observational by using descriptive method and total sampling technique . The data collection on characteristic and patients compliance was made through  a questionnaire. The data obtained were recapitulated and processed using the Chie Square SPSS 24 method in tabular form and presented in percentage form.The results showed that the relationship between gender P-value = 0.01, occupation P value = 0.065, education level p value = 0.330, on the level of compliance, where gender has a relationship with compliance p = 0.01 0.05 Ho rejected and Ha accepted, while the relationship between work p = 0.065 and education p = 0.330 on compliance tended to have no effect.